Measuring water adsorption processes of metal-organic frameworks for heat pump applications via optical calorimetry - Woellner, Michelle; Klein, Nicole; Kaskel, Stefan (Microporous and Mesoporous Materials, 2019)
Optical calorimetry (broadband IR-detection of the released heat of adsorption, “InfraSORP”) during water adsorption processes is used for an accelerated assessment of porous materials performance in heat pump applications. Metal-organic frameworks (MOFs) are screened as a highly promising class of materials for water adsorption driven heat exchangers with high water adsorption capacities. Based on a proper calibration, optical calorimetry is demonstrated to allow for rapid estimation of the total water adsorption capacity at a given relative humidity. In a dynamic mode, full water adsorption isotherms can be measured using a step-wise increase of the relative humidity. As cycling stability is among the most critical issues for the integration of new porous materials into systems, the InfraSORP methodology provides a valuable and inexpensive tool for accelerated cycling and stability testing. The InfraSORP technique is demonstrated to provide a significantly accelerated automated and easy-to-acquire alternative as compared to conventional characterization methods.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Adsorption heat pump; InfraSORP; Metal-organic frameworks; Optical calorimetry; Water adsorption